Grid Connected Inverter for Current Control by Using Anti-Islanding Technique - B V Rajanna; K S Srikanth (Institute of Advanced Engineering and Science, 2018)
The inverter with critical loads should be able to provide critical loads with a stable and seamless voltage during control mode change as well as clearing time. The indirect current control has been proposed for providing stable voltage with critical load during clearing time and seamless control mode transfer of inverters. However, the islanding detection is difficult since with the indirect current control the magnitude and frequency of voltage do not change when the islanding occurs. The conventional anti-islanding method based on the magnitude and frequency of voltage variation cannot apply to the indirect current control. This paper proposes an islanding detection method for the indirect current control. The proposed islanding detection method can detect the islanding using reactive power perturbation and observation when the frequency and magnitude of voltage don’t vary during clearing time. In order to verify the proposed anti-islanding method, the experimental results of a 600W three-phase inverter are provided.